Desencanto, amor y licor en los discursos comunicativos de la música popular ecuatoriana: el pasillo, yaraví y sanjuanito. - Capelo Capelo, Carlos Eduardo (2014)
Disenchantment, love and liquor in the communicative Ecuadorian popular musical speeches: Pasillo, Yaraví and Sanjuanito, this is an attempt for scanning the lyrics of these historical musical genres which have produced through the time the cultural musical diversity of Ecuador. In order of doing so, first of all it was necessary to do a bibliographical inspection of the communication theory to understand the evolution of the communication argument, culture and music in the social science. In the same way, it was indispensable to do an incursion into the history of the Ecuadorian music: a synthetic musical vision of the prehispanic cultures, the colonial time, during the republic time until nowadays. Besides this, the deep study of the distinctive details of the aforementioned rhythms. Subsequently, it was done a semantic analysis of the communicative speeches in selected themes (considering the lyrics and context in which they were developed), with their respective results, results that besides were sustained for qualified specialists. The polls carried out by the public were also an essential axis to support the thesis of this investigation, as well as the tabulation of the results for ratifying the subjective and collective opinion.